Formulations of linear low-density polyethylene-natural rubber (LLDP-NR) nanocomposite with high mechanical and dielectric strength for electrical insulation - Mohd Jamail, Nor Akmal; Sies, Mohamad Farid (Penerbit UTHM, 2020)
Electrical insulation plays an important role to protect high-voltage (HV) system from operation failure [1]. Electrical technology incorporates many different types of insulating materials for safety against electrical hazards. Materials like PVC, glass, asbestos, rigid laminate, varnish, resin, paper, Teflon or rubber are very good electrical insulators. These materials can insulate electrical conductors from electric. Several causes, such as electrical treeing and voids, can affect the functionality of insulators [2]. Thus, it is important for electrical insulating materials to have good tensile properties in addition to high dielectric strength and low dielectric constant [1]. Polymer nanocomposites are widely used for high voltage outdoor insulating application due to their efficient mechanical and electrical performance. Recently, Silicone Dioxide (SiO2), Titanium Dioxide (TiO2) and Montmorillonite (MMT) nanofillers are used as fillers because there are listed as the main nanofiller commonly used in mechanical insulation purpose due to the increases of effective activation energy. Natural rubber (NR) is used because the nature of the interphase is found to affect viscoelasticity and it develops several interphases with the linear low density polyethylene (LLDPE) matrix...